QASHQDARYO HUDUDIDA TARQALGAN ORTHETRUM SABINA (DRURY 1770), NINACHI TURINI TAKSONOMIYASI VA MORFOBIOLOGIYASI - Norqobilova , Zarina (Actual problems and prospects of the study of the fauna, 2024)
In this article, as a result of the monitoring of the odonata fauna of Kashkadarya during the years 2020-2023, the location, period, and morphobiology of the species Orthetrum sabina Drury 1770 belonging to the genus Orthetrum Newman, 1833 of the family Libellulidae are also presented.